Linguistic Features and Patterns of Texting: Results of a Case Study at an Indian University - Ali, Jamal Kaid Mohammed; Hasnain, S. Imtiaz; Beg, M. Salim (Theory and practice in language studies, 2021)
The main objective of the present study is to explore the linguistic features which characterize English used by texters. It also aims to investigate if texting follows any specific pattern. As this study aimed to investigate the linguistic features of texting and their impact on the structure of Standard English, the data of the study were collected from a sample of ninety students. The morphosyntactic elements, phonological elements and code mixing elements were linguistically analyzed separately, providing some examples from the data collected for the study. Although punctuation has been discussed under both morphosyntax and phonology, its significant presence in the data prompted us to look into the pragma-semantic elements in the use of punctuation by the texters. Five sent emails, five sent SMS and five sent Facebook chats from each of the respondents were collected to test the linguistic features of texting. SMS are more deviated from Standard English than Facebook chat texts in some cases such as deletion of subject and deletion of punctuation. It is found out that email texts were less deviated from Standard English than SMS and Facebook chat texts. It was found out that the respondents deviated from the Standard English in all the aspects which were examined, i.e. in morphosyntactic and phonological structures, which indicated that it could be a threat to Standard English. This study proved that texting followed some patterns in some cases but it was randomly used in other cases and it is difficult to control and find fixed patterns followed.